The Contribution of Technological Progress to Farm Output: 1950-75 - Ruttan, Vernon W. (The Review of Economics and Statistics, 1956)
R ECENT discussion of future farm output requirements ' have stressed heavily the important role which technological progress is expected to play in meeting the projected output requirements. This is as true of the studies which have emphasized the transitory nature of present food surpluses 2 as of the studies which point to continuation of the present pressure of food supplies on population. I In spite of this emphasis on the importance of technological change, these studies have generally failed to make explicit the relationship between technological progress and changes in factor input requirements other than labor inputs. This failure seems to stem from use of an analytical scheme which fails to distinguish between technological change and change in labor productivity, thus confusing the contributions to farm output made by technological change and increased nonlabor inputs.4 In this paper, I shall attempt (a) to outline an analytical scheme which distinguishes between the contributions of technological change and increased nonlabor inputs, (b) to present a set of alternative technological change and factor input models for American agriculture which will illustrate the possible consequences of alternative rates of technological change on certain aggregate input categories during the next quarter century, and (c) to discuss some questions of agricultural policy stemming from the close relationship between technological change and input requirements.